Therapeutic potential of isolated flavonoids from Anise and coriander aerial parts in antimicrobial efficacy, molecular docking, ADMET, and dynamic simulations - Salma El Sawi; Amal M. El-Feky; Mohamed Ibrahim El-Sayed; Ahmed F. El-Sayed (Scientific Reports)
Abstract Anise (Pimpinella anisum) and coriander (Coriandrum sativum) are globally esteemed for their applications in both culinary and medicinal contexts. In the present study, the quantitative analysis of total phenolic and flavonoid contents revealed that the aerial parts of anise contained elevated levels of phenolics (43.5 ± 0.23 mg/g) and flavonoids (39.8 ± 0.19 mg/g) in comparison to coriander, which exhibited values of 53.1 ± 0.18 mg/g for phenolics and 48.7 ± 0.21 mg/g for flavonoids. HPLC analysis revealed that quercetin was the most prevalent flavonoid, with chlorogenic acid and ellagic acid being the primary phenolic acids observed in both P. anisum and C. sativum. Eight flavonoids were isolated through column chromatography and silica gel thin-layer chromatography. The flavonoids identified from anise included isorhamnetin, kaempferol 3-O-rhamnoside, myricetin 3-O-rhamnoside, luteolin 7-O-β-D-glucopyranoside, and rutin, whereas coriander yielded quercetin, quercetrin, and kaempferol 3,7-O-dirhamnoside. Furthermore, the study highlighted the antimicrobial capabilities of anise and coriander extracts against pathogenic microorganisms, showing varying levels of effectiveness. Molecular docking was then utilized to examine interactions between promising compounds and antimicrobial target proteins. Results revealed that luteolin7-O-glucopyranoside, isorhamnetin, and quercetin exhibited strong binding energies, effectively binding to active sites of antimicrobial protein receptors. These interactions involved diverse molecular interactions, indicating the potential for enzyme inhibition and significant antimicrobial effects. Furthermore, in-silico ADMET profiles indicated alignment with Lipinski rules, suggesting advantageous physicochemical properties for these compounds. The MD simulations revealed stable complexes between luteolin7-O-glucopyranoside and antimicrobial receptors (1AD4, 2UV0, 2OV5, and 5TZ1). This stability was evidenced by RMSD values ranging from 0.18 to 0.40 nm, indicating minor fluctuations in RMSF values (0.10 to 0.60 nm). The SASA values ranged from 135 to 235 nm², and Rg values varied from 1.85 to 2.50 nm, offering insights into the protein complexes’ shapes. These results support the compounds’ potential in ongoing drug development efforts, highlighting their stability and suitability for further exploration in drug development processes.